If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = 2x + -5 Reorder the terms: 3(4 + x) = 2x + -5 (4 * 3 + x * 3) = 2x + -5 (12 + 3x) = 2x + -5 Reorder the terms: 12 + 3x = -5 + 2x Solving 12 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x 12 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 1x = -5 + 0 12 + 1x = -5 Add '-12' to each side of the equation. 12 + -12 + 1x = -5 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = -5 + -12 1x = -5 + -12 Combine like terms: -5 + -12 = -17 1x = -17 Divide each side by '1'. x = -17 Simplifying x = -17
| 49-10x=8x+23 | | 3x-12-x+2=2x-4 | | 2x+13=41-7x | | 7-9x=87-23x | | 2(2-x)=(x+3) | | -4-3x=14-19x | | 6=-10-p/5 | | -4(x+5)=28 | | 0-5=6-7x | | 0-5x=-7x | | -48=6(a-1) | | x+2x+x+25=165 | | 4+7x=34-x | | -57=-5x+8(3+4x) | | 5+8m=-1+5m | | 6x-5=4x-53 | | y=.666x-1 | | 6x-4x+7=0 | | 4x-2(x+3)=3x | | 63=-7(3n-3) | | X=-3.6X^2-8.8X+8.3 | | 6x-3(4+x)=0 | | 4x=-25 | | 47533.32=2*3.14*r^2+2*3.14*r*232 | | f/5+4=29 | | -2(9-3x)+2=-4 | | -73=6m-5(m-3) | | 7-3(2-x)+6=-2 | | 72*64-7/80+4*x=40*52*2 | | -6(x-3)-8=-8 | | 3265+28=oshawn | | 4=4a-8(a-2) |